Planning of single-used mask waste containers as personal protective equipment: a case study of Jakarta City station - Mega Mutiara Sari; Michael Yosafaat; Annisa Kamilia Nastiti; Iva Yenis Septiariva; Reifaldy Tsany Betta Aryanto; Yesaya Emeraldy Priutama; I Wayan Koko Suryawan; Sapta Suhardono (Intelektual Pustaka Media Utama, 2022)
During the COVID-19 pandemic, the use of masks is an obligation for everyone to maintain the transmission of the virus to fellow humans. Public places such as stations are one of the locations that may produce single-use masks as personal protective equipment waste. This study aimed to plan the most appropriate type of infectious waste container for disposable masks. Storage with the addition of ultraviolet lamp technology is one way to increase virus removal efficiency compared with no further processing. In this study, it was estimated that the most appropriate container volume is with a capacity of 50 L per station. The collection must be done every 24 hours; the estimated cost for one container can reach IDR 1,988,900. This planning can reduce the amount of mask waste used for the environment and reduce the burden applied to these places at the end.